Reassessment of Mendelian gene pathogenicity using 7,855 cardiomyopathy cases and 60,706 reference samples - Roddy Walsh; Kate Thomson; James S. Ware; Birgit Funke; Jessica Woodley; Karen McGuire; Francesco Mazzarotto; Edward Blair; A Seller; Jenny C. Taylor; Eric Vallabh Minikel; Daniel G. MacArthur; et al. (2016)
Abstract The accurate interpretation of variation in Mendelian disease genes has lagged behind data generation as sequencing has become increasingly accessible. Ongoing large sequencing efforts present huge interpretive challenges, but also provide an invaluable opportunity to characterize the spectrum and importance of rare variation. Here we analyze sequence data from 7,855 clinical cardiomyopathy cases and 60,706 ExAC reference samples to better understand genetic variation in a representative autosomal dominant disorder. We show that in some genes previously reported as important causes of a given cardiomyopathy, rare variation is not clinically informative and there is a high likelihood of false positive interpretation. By contrast, in other genes, we find that diagnostic laboratories may be overly conservative when assessing variant pathogenicity. We outline improved interpretation approaches for specific genes and variant classes and propose that these will increase the clinical utility of testing across a range of Mendelian diseases. One Sentence Summary Comparing the frequency of very rare variation between patient cohorts and very large genomic reference datasets enables the reliable re-evaluation of genes previously implicated in Mendelian disease and more accurate assessment of the likely pathogenicity of different classes of variants.